Asociatividad de pequeños agricultores y exportación en la región peruana de Cajamarca - Valdiglesias Oviedo, Jhon (2024)
This research aims to analyze to what extent associativity will allow small Peruvian farmers to enter, grow and maintain themselves in the international market. For this we focus on the Cajamarca region; for being one of the recent leaders in terms of organic coffee exports due to the coffee associations that have been formed. To measure the impact of associativity on exports, a logistic regression model is employed, having as a source of information the IV National Agricultural Census; which allows to construct all the mentioned variables. The results are robust and confirm the hypothesis of this research.